A new species of Phasmahyla Cruz, 1990 from the Atlantic Forest in the state of Rio de Janeiro, Brazil (Amphibia, Hylidae, Phyllomedusinae) - de Carvalho-E-Silva, Ana Maria Paulino Telles; Da Silva, Guilherme Ramos; Carvalho-E-Silva, Sergio Potsch (Zootaxa, 2009)
A new species of the genus Phasmahyla Cruz, 1990 is described from the state of Rio de Janeiro in southeastern Brazil, and is compared with the other six species of the genus. The new species, Phasmahyla cruzi, is characterized by its small size, males measuring from 30.5 mm to 34.2 mm, and a female 41.6 mm; smooth skin; inner parts of legs and flanks slightly orange-colored, with numerous small, round, violet blotches; inner areas of the hands and feet slightly orange, and outer areas green with small round violet blotches; tympanum partially covered by the supratympanic fold; snout short and truncated; large eyes; palpebral membrane with white reticulation, pigmented over their entire area; combined lengths of the femur and tibia are greater than the mean snout-vent length; tarsus large, with the outer margin smooth or slightly crenulated; males with a visible nuptial pad from the base of the first finger to the inner carpal tubercle; tadpoles with one to three white spots on the distal third of the tail musculature; tail fins higher than the body, tail length equal to 67% of total body length; oral disc large and wide, with reduced indentation on dorsal margin and no indentation on ventral margin; tooth row formula 0-1/2(1); total length from 40.1 mm to 46.4 mm in stage 37. The new species was found above 200 m asl, from the municipalities of Mangaratiba to Parati, state of Rio de Janeiro.